CARBON RECYCLED INTO DEEP EARTH: EVIDENCE FROM DOLOMITE DISSOCIATION IN SUBDUCTION-ZONE ROCKS - Zhu Y.; Ogasawara Y. (My University, 2002)
The dolomite-dissociation textures documented here in rocks from the Kokchetav ultrahigh-pressure massif suggest that the experimentally expected dolomite dissociation happened in the subducted slabs represented by these rocks. Two reactions, magnesite = C + MgO + O2, and majoritic garnet + MgO + H2O = garnet + clinochlore, recorded in carbonate inclusions and the host majoritic garnet are responsible for generation of graphite and clinochlore during the exhumation. The dolomite dissociation indicates that carbonate materials were subducted to depths of >250 km below Earth's surface. Such deep subduction evidently brings abundant carbon and carbonate into deep Earth.
Keywords: dolomite; aragonite; clinochlore; diamond; graphite; carbon recycling; subduction